Association of sarcoidosis and ulcerative colitis: a review of 20 cases - Jarrot, Pierre André; Dury, Sandra; Rakotomalala, Arilanto; Vella-Boucaud, Juliette; Patey, Martine; Deslee, Gaetan; Lebargy, François (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Sarcoidosis and ulcerative colitis is a rare association. We report a case of this association and describe its clinical, radiological and functional characteristics based on a review of the literature. This association must be recognized by the physician and must be clearly distinguished from a systemic site of ulcerative colitis or drug-related pneumonitis.